2015
DOI: 10.1002/bmc.3579
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of pharmacokinetic interaction between piracetam and l‐carnitine in healthy subjects

Abstract: A rapid, sensitive and specific method for quantifying piracetam in human plasma using Piracetam d-8 as the internal standard (IS) is described. The analyte and the IS were extracted from plasma by one-step precipitation of protein using an acetonitrile (100%). The extracts were analyzed by high-performance liquid chromatography coupled with electrospray tandem mass spectrometry (HPLC-MS/MS). The method had a chromatographic run time of 3.8 min and a linear calibration curve over the range 0.5-50 µg/mL (r > 0.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…Another impurity CTTA was not quantified because the standard is unavailable. Numerous reports on analytical methods for determination of l‐ carnitine in biological samples (plasma, serum, and urine), food supplements and pharmaceutical formulations have been published , but there are few reports on determining the impurities in l‐ carnitine. CTEA (crotonoylbetaine) was detected in pharmaceutical formulations of l‐ carnitine by ion pairs HPLC–UV, with the content at < 1% .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Another impurity CTTA was not quantified because the standard is unavailable. Numerous reports on analytical methods for determination of l‐ carnitine in biological samples (plasma, serum, and urine), food supplements and pharmaceutical formulations have been published , but there are few reports on determining the impurities in l‐ carnitine. CTEA (crotonoylbetaine) was detected in pharmaceutical formulations of l‐ carnitine by ion pairs HPLC–UV, with the content at < 1% .…”
Section: Resultsmentioning
confidence: 99%
“…Other columns, such as HILIC columns, have also been used to determine carnitine and acylcarnitines in milk, human urine, serum, and plasma . A CN analytical column was used for analysis of piracetam and l‐ carnitine in human plasma .…”
Section: Introductionmentioning
confidence: 99%
“…However, the studies have shown the drugs have good bioavailability in conjunction and act in concentrations below the needed ones to act individually. 10,18 Costa RAP et al 10 further found that the drugs act on mitochondrial metabolism, preventing and/or improving mitochondrial dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…They are focused on the assessment of pharmacokinetic interaction between PIR and l-carnitine in human plasma using piracetam d-8 as the internal standard and one-step precipitation of protein using acetonitrile. The extracts were analyzed by HPLC-MS/MS [94]. The HPLC methods describe using a mixture of an aqueous solution of perchloric acid, methanol or acetonitrile with protein precipitation and LLE with chloroform, 2-propanol, toluene or hexane mixture as a form of simple extraction [95,96].…”
Section: Piracetammentioning
confidence: 99%